Diversity of Waterbirds from Coastal Agroecosystem, Central Kerala, India - Neena Narayanan (Current Advances in Geography, Environment and Earth Sciences Vol. 7, 2022)
Coastal Agroecosystem (Pokkali Farming) has been identified with a high waterbird density. In this study, we analysed the waterbird diversity and their current threats in Pokkali farming during February 2021- January 2022. Bird survey was carried out using the Direct Observation Method, Point Count Method and Line Transect Method. A total of 31 species of waterbirds belonging to 8 orders and 14 families were recorded. All bird species are included in Least Concern of the IUCN Category except three species. Three bird species are Globally Threatened ones and these are recorded from Pokali wetland. They are: Oriental Darter (Anhinga melanogaster), Spot-billed Pelican (Pelecanus philippensis) and Black headed Ibis (Threskiornis melanocephalus). Most threats to birds are the cause of human actions. The leading threats observed in our sampling site are Habitat destruction, Electric lines, Fishing nets inside the water affects mainly cormorants, Feral dogs and other Predators, Communication tower, flood, climate change, hunting of waterbirds, loss of employees, Solid waste, plastics, water hyacinth, water and soil pollution.